Rare Proteus mirabilis Aortic Valve Infective Endocarditis without a Urinary Tract Infection. (31st December 2022) - Gorn, Sarah; Talley, Nicholas; Mitchell, Austin; Pineda, Alejandro
Abstract : Proteus mirabilis infective endocarditis is a rare disease with only 17 reported cases. It is typically associated with urinary tract infections (UTIs), staghorn calculi, and/or asymptomatic bacteriuria. We present a case of a 73-year-old male who presented with positive blood cultures for Proteus mirabilis but with a negative urinalysis and urine culture. He presented with acute renal failure and required hemodialysis. TTE was remarkable for a 30% ejection fraction, and no vegetations were visualized. TEE demonstrated a small vegetation on the left aortic valve. The initial urine culture remained negative throughout his hospitalization. He was treated with IV antibiotics and discharged without hemodialysis.